2016
DOI: 10.1002/iub.1526
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, andIn vitroantituberculosis activity of 2(5H)-Furanone derivatives

Abstract: A series of 2(5H)-furanone-based compounds were synthesized from commercially available mucohalic acids. From the first-generation compounds, three showed inhibitory activity (10 mg/mL) of at least 35% against Mycobacterium smegmatis mc 2 155 growth (Bioscreen C system). In screening the active first-generation compounds for growth inhibition against Mycobacterium tuberculosis H37Rv, the most active compound was identified with a minimum inhibitory concentration (MIC 99 ) of 8.07 mg/mL (15.8 mM) using BACTEC 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Regarding the compound structure, ZB5-1 has a furanone ring system. Also known as butyrolactone or butanolide, ZB5-1 is a widely recognized component of natural products, exhibiting an extensive spectrum of pharmacological activities [ 45 ]. Moreover, a quantitative structure-activity relationship (QSAR) analysis assessed that furanone derivatives would be a potential inhibitor of COX-2 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the compound structure, ZB5-1 has a furanone ring system. Also known as butyrolactone or butanolide, ZB5-1 is a widely recognized component of natural products, exhibiting an extensive spectrum of pharmacological activities [ 45 ]. Moreover, a quantitative structure-activity relationship (QSAR) analysis assessed that furanone derivatives would be a potential inhibitor of COX-2 [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they selected six structures, which weree valuated in the HCV sub-genomic replicon assay,a nd of these six, the best hit, compound 30 (Figure 7), was found to inhibitt he HCV replicon replication in the low micromolar range. [76] In 2015, Akhter et al identified quinoline-substituted furanone derivatives as selective falcipain-2 inhibitors and evaluated their antimalarialp otential. [74] In 2016, Khokra et al prepared al ibrary of 24 quinolinebased butenolides (furanones) and their nitrogen analogues.…”
Section: Pharmacological Profile Of Furanonederivativesmentioning
confidence: 99%
“…From the second series, two compounds were reported to possess improved antitubercular activity against M. tuberculosis H37Rv. [76] In 2015, Akhter et al identified quinoline-substituted furanone derivatives as selective falcipain-2 inhibitors and evaluated their antimalarialp otential. Mosto ft he synthesised compoundsw ere reportedt ob es ignificantly potent with their activity being less than 5 mgmL À1 .T heir preliminary structure-activity relationship study suggested that increasing the electropositive character increased the antimalarial activity.I nt his work, Akhter et al hypothesised falcipain-2 as ap otential targetfor their compounds and hence,also performed molecular docking studies of the compounds with falcipain-2, which revealed vital interactions and theirb inding conformation.…”
Section: Pharmacological Profile Of Furanonederivativesmentioning
confidence: 99%
“…These compounds were originally described as a natural tool of red algae Delisea pulchra , repressing its biofouling [6,7]. It has been shown that various furanones can either be produced naturally by a variety of microorganisms and plants or synthesized chemically [8,9,10]. In cells, furanones participate in intra- and inter-species signaling and communication, and act as attractants, pheromones, and antimicrobials [11].…”
Section: Introductionmentioning
confidence: 99%